ВЛИЈАНИЕТО НА ТУРСКИОТ ЈАЗИК ВРЗ МАКЕДОНСКИОТ ЈАЗИК (Philological Studies, 2019)
The influence on the Turkish language on the Macedonian can be traced from the 16 century, when in the translations were included elements from the Macedonian vernacular, till now, in conditions of successfully completed standardization of the Macedonian language. The Turkish language also influenced Macedonian phonetics, morphology and lexicology. The Turkish influence on the Macedonian phonetic system is mostly felt in the following areas: sustaining and affirmation of phonemes in the process of disappearing, palatalization of certain phonemes and introduction of new phonemes. The influence of the Turkish on the morphological system of the Macedonian language is particularly evident in the following areas: introduction of new suffixes, unchangeable and intensified adjectives and differentiation of past simple and progressive. The influence of the Turkish on the lexicological system of the Macedonian could be felt in every area, but only those lexical borrowings that were connected with everyday experiences and which did not have an equivalent.